Relationship Between Social Support and Academic Stress in Islamic High School: Hubungan Antara Dukungan Sosial dan Stres Akademik di Sekolah Menengah Islam - Intani, Anggun Hastika; Ansyah, Eko Hardi (Indonesian Journal of Islamic Studies, 2025)
General background: Academic stress is a common psychological challenge faced by adolescents, often influenced by social and environmental demands. Specific background: Previous studies suggest that social support contributes to students’ well-being, yet its association with academic stress in Islamic school contexts remains underexplored. Knowledge gap: Limited evidence exists regarding the relationship between social support and academic stress among high school students in faith-based educational settings. Aim: This study examines the correlation between social support and academic stress among students at SMA Al-Islam Krian. Results: Using a quantitative correlational design, data were collected from 213 randomly selected students out of a population of 1,308, measured with Likert scales and analyzed with SPSS correlation tests. Findings revealed a weak but significant negative correlation (r = -0.225, p = 0.001 < 0.005), indicating that higher social support is associated with lower academic stress. Novelty: The study highlights the role of social support in reducing academic stress within the context of Islamic education. Implications: Strengthening peer and community support systems may help students manage academic demands and maintain psychological well-being. Highlights: Weak but significant negative correlation between social support and stress. Novel insight from students in an Islamic high school context. Practical implications for improving support systems in education. Keywords: Academic Stress, Social Support, Adolescents, Psychological Well-being, Islamic Education